A comparison of the reliability and validity of SF-6D, EQ-5D and HUI3 utility measures in patients with schizophrenia and patients with depression in Singapore. (April 2019) - Abdin, Edimansyah; Chong, Siow Ann; Seow, Esmond; Peh, Chao Xu; Tan, Jit Hui; Liu, Jianlin; Hui, Sophia Foo Si; Chua, Boon Yiang; Sim, Kang; Verma, Swapna; Vaingankar, Janhavi Ajit; Subramaniam, Mythily
Highlights: The SF-6D has good reliability, validity and magnitude of change in scores than other measures in the schizophrenia sample. The HUI3 has good reliability, validity and magnitude of change in scores than other utility measures in the depression sample. We suggest that the SF-6D and HUI3 are suitable as a utility measure for patients with schizophrenia and depression in a multi-ethnic Asian population. Abstract: There is limited evidence of a direct comparison of the psychometric performance of generic preference-based measures in patients with mental illness in an Asian patient population. The current study aimed to compare the test–retest reliability, convergent and known-group validity and magnitude of change in scores of the EuroQol Five-Dimension, Health Utility Index Mark 3 (HUI3) and Short-Form Six-Dimension (SF-6D) measures in patients with depression and patients with schizophrenia spectrum disorder. 500 patients were recruited from a tertiary psychiatric institution in Singapore. The Schizophrenia Quality of Life Scale (SQLS), 8-item Patient Health Questionnaire, Quality of Life Enjoyment and Satisfaction Questionnaire (Q-LES-Q), and Positive and Negative Syndrome Scale were also included. In the schizophrenia sample, the SF-6D was found to have higher test–retest validity, convergent validity with SQLS domain scores, known-group validity and magnitude of change in scores over 6-month follow up than other measures. In the depression sample, the HUI3 was found to have higher test–retest reliability, convergent validity with Q-LES-Q, known group validity and magnitude of change in scores than other measures. Results suggest that the SF-6D and HUI3 to be more suitable as a utility measure for patients with schizophrenia and depression in an Asian patient population.